By other means: judicial decisions as a continuation of the politics in the jurisprudence of the Supreme on the Writ of Injunction - Fulgêncio, Henrique Augusto Figueiredo (Revista de Ciências Sociais, 2018)
This article analyzes the role played by Brazilian Federal Supreme Court members in the Writ of Injunction´s creating and recasting process. Based on the analysis of the opinions informally issued by the justices to the press during the constituent process of 1987-1988, as well as the leading cases on Writ of Injunction, it holds that the abovementioned justices were key political actors in the Writ of Injunction’s neutralizing process. For this purpose they adopted 3 successive strategies: to influence the Constituent Assembly´s members to restrain said institute; to delay the Writ of Injunction’s enforcement until its legal regulation takes place; and to restrict its effects through creative interpretation. Through these strategies, the political dispute over the Writ of Injunction was extended to the judicial scope, which remains in dialogue with the legislative sphere under the leadership of the Supreme Court members.